STUDY OF THE INFLUENCE OF SOME ADDITIVES ON THE RATE OF HYDROGEN PEROXIDE DECOMPOSITION IN ALKALINE MEDIUM: I. INFLUENCE OF UNSATURATED CYANOLACTON AND DIMETHYL SULFOXIDE (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The influence of 2-cyano-3,4,4-trimethyl-2-butene-4-olyd (unsaturated cyanolacton, UCL) and DMSO on the rate of the reaction H2O2+HOO– at room temperature was studied using gasometric method. Taking into consideration the solubility of H2O2 in water and solubility of UCL in oil, the UCL influence is studied in: a) water–EtOH solution; b) in water emulsions stabilized by either anionic (sodium dodecylsulfate, DDS) or cationic (dodecyltrimethylammonium chloride, DTAC) emulsifier. It is assumed that very polar groups, which are in UCL and DMSO molecules, favor the non-radical mechanism of the reaction.
Keywords: anionic emulsifier, cationic emulsifier, non-radical mechanism of the reaction